Are cinema, TV and football recommended for Muslims?: The Millî Görüş movement’s view on popular culture - Rosenberg, Uri (Middle Eastern studies, 2023)
This article charts changes in the views towards popular culture of the most prominent Turkish-Islamist movement that operated in the late twentieth century, the Millî Görüş (‘The National Outlook’), a movement that altered Turkey’s history and brought up its current Islamist leader - Recep Tayyip Erdoğan. Through a unique and intensive analysis of Millî Görüş texts and documents, the article follows significant changes in Millî Görüş discourse regarding three forms of popular culture - cinema, television, and spectator sports - from the 1970s - when these forms of popular culture were warned against - to the 1990s - when the movement recommended engaging with such culture. This article argues that these changes reflect a greater change in the movement’s views on how Muslims should live their lives. Lastly, the paper suggests these changes may have occurred due to three main reasons: (1) deciding strategically to not resist the growing availability and appeal of popular culture; (2) the movement’s wish to win the Turkish elections, which required them to appeal also to less pious Turks, and (3) the gradual appearance of alternative, ‘Islamic’ popular culture in Turkey - one which the Millî Görüş felt comfortable to promote.